Analisis Faktor Penyebab Keterlambatan Pelaporan di Core Tax dan Dampaknya (Studi Kasus pada PT Mitra Karya Prima) - Difta Maulia Nasywa; Febry Fabian Susanto (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze the factors contributing to delays in tax reporting through the Core Tax Administration System (CTAS) and their impacts on administrative efficiency and taxpayer compliance at PT Mitra Karya Prima. CTAS is a digital system developed by the Directorate General of Taxes since 2025 as part of the technology-based transformation of tax services. The study employs a descriptive, qualitative approach using a single-case study design, with data collected through in-depth interviews, direct observation, and document analysis of tax reporting for the period from January to July 2025. The findings identify three main factors causing reporting delays: (1) technical system issues, including server disruptions and unstable module integration; (2) human resource factors, particularly limited digital literacy and insufficient technical training; and (3) regulatory and administrative complexity arising from frequent regulatory updates without adequate technical guidance. These conditions adversely affect administrative efficiency, increase the risk of tax sanctions, and reduce taxpayer trust in digital tax systems. The study underscores the importance of strengthening technological infrastructure, enhancing human resource capacity, and simplifying regulations to support the effectiveness and sustainability of CTAS implementation.